Biomechanical Study of Trapezoidal Plate, Delta Plate and Miniplate in Subcondylar Fracture - JYOTISH SAIKIA; SANJEEV KUMAR; HARSH JAIN; AMIT GUPTA (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Condylar fracture accounts for 25-35% of all mandibular fracture. When it comes to open reduction and internal fixation, the design of the plate plays a crucial role to withstand the amount of masticatory force in the condylar region. Aim: To evaluate the biomechanical stability of osteosynthesis using the Trapezoidal plate, Delta plate and Miniplate in subcondylar fracture. Materials and Methods: The condyle of 36 porcine hemimandible was osteotomized at a defined location with the help of a jig. Three groups A, B, C were created and each group had 12 hemimandibles. Group A was fixed with trapezoidal plate, group B was fixed with delta plate and group C was fixed with 2 four-hole miniplates. Each group was subjected to a linear loading using a Universal Testing Machine (UTM) in four different directions. The direction of the force used was from lateral to medial, medial to lateral, anterior to posterior and posterior to anterior was indicated using (1,2,3,4) respectively. Yield load and yield displacement were measured for the trapezoidal plate, delta plate and miniplate. Means were derived and compared for statistical analysis using the Kruskal-Wallis test and Mannwhitney U test with a confidence level of 95%. Results: None of the plates fractured. Screw loosening was seen in one delta plate and in two miniplate. In posterior to anterior and from medial to lateral the trapezoidal plate tolerated the highest load. From anterior to posterior and lateral to medial the miniplate tolerated the maximum load. Statistically significant difference was seen for yield load and no difference was seen for yield displacement in three groups. Conclusion: This biomechanical study indicates that like miniplate, trapezoidal and delta plates exhibit stable osteosynthesis for subcondylar fractures. The trapezoidal and delta plate has the advantages of providing three dimensional stability using single plates.